High control rates of proton- and carbon-ion-beam treatment with intensity-modulated active raster scanning in 101 patients with skull base chondrosarcoma at the Heidelberg Ion Beam Therapy Center - Mattke, Matthias; Vogt, Kira; Bougatf, Nina; Welzel, Thomas; Oelmann-Avendano, Jan Tobias; Hauswald, Henrik; Jensen, Alexandra; Ellerbrock, Malte; Jäkel, Oliver; Haberer, Thomas; Herfarth, Klaus; Debus, Jürgen; et al. (Cancer, 2018)
BACKGROUND The current study compares the results of irradiation with protons and irradiation with carbon ions via a raster scan technique in patients with G1 and G2 skull base chondrosarcomas. METHODS Between 2009 and 2014, a total of 101 patients (40 men and 61 women) with a median age of 44 years (range, 19-77 years) were irradiated with carbon ions (79 patients) or protons (22 patients) via a raster scan technique at the Heidelberg Ion Beam Therapy Center. The median total dose was 60 Gy (relative biological effectiveness [RBE]) at 3 Gy per fraction for carbon ions and 70 Gy (RBE) at 2 Gy per fraction for protons. The median boost planning target volume was 38 cm3 (range, 8-133 cm3). Overall survival (OS) and local control (LC) were evaluated with the Kaplan-Meier method. RESULTS The median follow-up period was 40 months (range, 0.8-78.1 months). At the start of the irradiation, all patients had residual macroscopic tumors. Five patients (5%) developed a local recurrence during the follow-up. The 1-, 2-, and 4-year LC rates were 100%, 100%, and 100%, respectively, for protons and 98.6%, 97.2%, and 90.5%, respectively, for carbon ions. The OS rates during the same periods of time were 100%, 100%, and 100%, respectively, for protons and 100%, 98.5%, and 92.9%, respectively, for carbon ions. An age ≤ 44 years was associated with a trend for a better outcome. No toxicity worse than Common Toxicity Criteria grade 3 was observed after treatment. CONCLUSIONS No significant difference between carbon ions and protons in the therapy of skull base chondrosarcoma could be detected in these initial retrospective results. Cancer 2018;124:2036-44. © 2018 American Cancer Society.